Parallel Construction of Orthologous Sequence-Ready Clone Contig Maps in Multiple Species - Thomas, James W.; Prasad, Arjun B.; Summers, Tyrone J.; Lee-Lin, Shih-Queen; Maduro, Valerie V.B.; Idol, Jacquelyn R.; Ryan, Joseph F.; Thomas, Pamela J.; McDowell, Jennifer C.; Green, Eric D.

(untitled) (Genome Research, 2002)
Comparison is a fundamental tool for analyzing DNA sequence. Interspecies sequence comparison is particularly powerful for inferring genome function and is based on the simple premise that conserved sequences are likely to be important. Thus, the comparison of a genomic sequence with its orthologous counterpart from another species is increasingly becoming an integral component of genome analysis. In ideal situations, such comparisons are performed with orthologous sequences from multiple species. To facilitate multispecies comparative sequence analysis, a robust and scalable strategy for simultaneously constructing sequence-ready bacterial artificial chromosome (BAC) contig maps from targeted genomic regions has been developed. Central to this approach is the generation and utilization of “universal” oligonucleotide-based hybridization probes (“overgo” probes), which are designed from sequences that are highly conserved between distantly related species. Large collections of these probes are used en masse to screen BAC libraries from multiple species in parallel, with the isolated clones assembled into physical contig maps. To validate the effectiveness of this strategy, efforts were focused on the construction of BAC-based physical maps from multiple mammalian species (chimpanzee, baboon, cat, dog, cow, and pig). Using available human and mouse genomic sequence and a newly developed computer program (soop) to design the requisite probes, sequence-ready maps were constructed in all species for a series of targeted regions totaling ∼16 Mb in the human genome. The described approach can be used to facilitate the multispecies comparative sequencing of targeted genomic regions and can be adapted for constructing BAC contig maps in other vertebrates.